2005
DOI: 10.1242/dev.01782
|View full text |Cite
|
Sign up to set email alerts
|

The homeodomain protein PAL-1 specifies a lineage-specific regulatory network in theC. elegansembryo

Abstract: analysis demonstrates that the identified PAL-1 target genes affect specification, differentiation and morphogenesis of C-lineage cells. In particular, we show that cell fate-specific genes (or tissue identity genes) and a posterior HOX gene are activated in lineage-specific fashion. Transcription of targets is initiated in four temporal phases, which together with their spatial expression patterns leads to a model of the regulatory network specified by PAL-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
184
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(192 citation statements)
references
References 51 publications
7
184
1
Order By: Relevance
“…Microarray and serial analysis of gene expression data combined with homeotic mutants (12,13), RNA enrichment methods (14), or FACS sorting of individual cells (15) reveal active genes within particular cells or stages of development. In situ hybridization (16) can localize mRNAs to particular stages and tissues.…”
mentioning
confidence: 99%
“…Microarray and serial analysis of gene expression data combined with homeotic mutants (12,13), RNA enrichment methods (14), or FACS sorting of individual cells (15) reveal active genes within particular cells or stages of development. In situ hybridization (16) can localize mRNAs to particular stages and tissues.…”
mentioning
confidence: 99%
“…lineages into muscle by PAL-1 activity, hlh-1 expression is positively regulated by PAL-1 (Baugh et al 2005a;Fukushige and Krause 2005). Baugh et al (2005a) identified hlh-1 in a microarray analysis of mRNA expression aimed at identifying PAL-1 transcriptional regulatory targets using mutant embryos with either no [pie-1 −/− ; pal-1(RNAi)] or excess PAL-1 activity [mex-3 −/− ; skn-1(RNAi)], and in the same experiment unc-120 and hnd-1 were also identified.…”
Section: Redundant Specification Of Muscle By Hlh-1 Unc-120 and Hnd-1mentioning
confidence: 99%
“…Baugh et al (2005a) identified hlh-1 in a microarray analysis of mRNA expression aimed at identifying PAL-1 transcriptional regulatory targets using mutant embryos with either no [pie-1 −/− ; pal-1(RNAi)] or excess PAL-1 activity [mex-3 −/− ; skn-1(RNAi)], and in the same experiment unc-120 and hnd-1 were also identified. Using reporter gene analysis and RNAi of pal-1 and its repressor mex-3; hlh-1, unc-120, and hnd-1 were each shown to be expressed in early embryonic myoblasts under the control of PAL-1 (Baugh et al 2005a).…”
Section: Redundant Specification Of Muscle By Hlh-1 Unc-120 and Hnd-1mentioning
confidence: 99%
See 2 more Smart Citations